Planning strategies for rural family farming enterprises in Mossoró, State of Rio Grande do Norte, Brazil (Research, Society and Development, 2020)
The management of rural activities is indispensable for the producer, as it provides adequate basis for the processes involved in this follow-up, which enables the improvement of the productive establishment, focusing on the main needs, achieving satisfactory economic and financial results. Thus, this study aimed to evaluate the planning strategies of family farming rural enterprises in the municipality of Mossoró, in the state of Rio Grande do Norte, considering the social and economic importance that this activity has for the region. The exploratory study took place through structured qualitative and quantitative questionnaires applied by technicians of the Sertão Entrepreneur Project. According to the results obtained, it was observed that 41% of the analyzed properties carry out production planning, both strategic and operational. That personal planning is carried out in strategic aspects at 53% and operational at 32%. Regarding financial planning, 28% of the enterprises stated that they performed strategically and 34% operationally. Therefore, it is possible to observe some points that may contribute to the lack of planning of the rural enterprises that should be better worked, among them we can mention, lack of guidance, discouragement with the activity and a large amount of risk to which these enterprises are exposed. planning the alternative to make these activities safer.